A search for an excited muon decaying to a muon and two jets in pp collisions at s=8TeV with the ATLAS detectoratlas.publications@cern.ch. (11th July 2016) - Aad, G; Abbott, B; Abdallah, J; Abdinov, O; Abeloos, B; Aben, R; Abolins, M; AbouZeid, O S; Abramowicz, H; Abreu, H; Abreu, R; Abulaiti, Y; et al.
Abstract: A new search signature for excited leptons is explored. Excited muons are sought in the channel pp â†' Î¼ Î¼ * â†' Î¼ Î¼ jet jet, assuming both the production and decay occur via a contact interaction. The analysis is based on 20.3 fb âˆ'1 of pp collision data at a centre-of-mass energy of s = 8 TeV taken with the ATLAS detector at the large hadron collider. No evidence of excited muons is found, and limits are set at the 95% confidence level on the cross section times branching ratio as a function of the excited-muon mass m Î¼ * . For m Î¼ * between 1.3 and 3.0 TeV, the upper limit on Ïƒ B ( Î¼ * â†' Î¼ q q Ì„ ) is between 0.6 and 1 fb. Limits on Ïƒ B are converted to lower bounds on the compositeness scale Î›. In the limiting case Î› = m Î¼ *, excited muons with a mass below 2.8 TeV are excluded. With the same model assumptions, these limits at larger Î¼ * masses improve upon previous limits from traditional searches based on the gauge-mediated decay Î¼ * â†' Î¼ Î³ .